If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 5 = -4x + 2 Reorder the terms: 5 + -7x = -4x + 2 Reorder the terms: 5 + -7x = 2 + -4x Solving 5 + -7x = 2 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 5 + -7x + 4x = 2 + -4x + 4x Combine like terms: -7x + 4x = -3x 5 + -3x = 2 + -4x + 4x Combine like terms: -4x + 4x = 0 5 + -3x = 2 + 0 5 + -3x = 2 Add '-5' to each side of the equation. 5 + -5 + -3x = 2 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = 2 + -5 -3x = 2 + -5 Combine like terms: 2 + -5 = -3 -3x = -3 Divide each side by '-3'. x = 1 Simplifying x = 1
| 13y+10y-5y= | | -162+36x+6x^2=0 | | 16=3l+2w | | 4a+2b-10a+2b= | | 16=-3x+10 | | 3(y-2)=-3(y-3) | | 2x-14=5x+7 | | m^2-75=-11 | | 8x+5y=53 | | -3y(6y+4)+2(3y-10)= | | 19x+13x+7x= | | 20x=2y+10 | | 48x^2-35=0 | | 9x^2-9=-131 | | -3+10=-4 | | (x+23)+(4x+17)+80=180 | | k^4-8=6p | | X+56=64 | | 4x+y+2z=14 | | ((X-3)/(x^2))=((x-3)/(x^2-1)) | | 6x^2+28x-2=0 | | 2(2x+4)=2x+9 | | 17-2=-3 | | 3(2x+6)=4x+3 | | 3(-3)-1/2y=2 | | 3z^2+3=6z | | 3z^2+3=6 | | x^2=725 | | 3(0)-1/2y=2 | | 3(-1)+2y=2 | | 3(-2)-1/2y=2 | | Y-5=0(x+2) |